Indonesia's Commitment to Combating the Crime of Terrorism through Diplomatic Communication and Global Development Cooperation: Papua KKB Case Study - Wahidah, Tuhfahtu Hasanatul; Pamungkas, Ananda Triaji; Amanusa, Nicky Felix (Journal of Indonesian Social Sciences and Humanities, 2024)
This research analyzes Indonesia's commitment to dealing with terrorist crimes through communication diplomacy and global development cooperation, with a main focus on the case of Kelompok Kriminal Bersenjata (KKB) in Papua. This research uses a qualitative approach using Internet based research methods which use the Internet as a source of data and information search to explore the role of the Indonesian government in responding to the threat of terrorism aimed at the KKB in Papua. The results of this research highlight various policies that have been implemented, such as the determination of KKB actions as criminal acts of terrorism based on the Law No. 5 of 2018, the implementation of international diplomacy, and also multilateral cooperation efforts, such as ASEAN Convention on Counter-Terrorism (ACCT). Increasing the status of the KKB as an act of terrorism encourages the government to be more able to act without being limited to handling ordinary criminal acts so that a more intensive approach to counter-terrorism measures can be taken. Even though the Government has taken many significant actions, challenges such as the geographic conditions of Papua, the ownership of automatic weapons by the KKB, as well as pressure from the international community, especially Pacific countries, are challenges that make efforts to resolve this conflict even more complex. This research recommends improving development communication strategies that can be more inclusive and humane as well as increasing international cooperation to maintain the stability and security of Papua. Diplomatic communication plays an important role in building dialogue channels between countries, international organizations and non-state parties. In this way, a long-term, sustainable resolution can be achieved, not only using a military approach but also political dialogue and socio-economic development.